A three-dimensional structure iron-doped cobalt-molybdenum oxide composite material, a preparation method and application thereof

CN113457689BActive Publication Date: 2026-10-13ZHEJIANG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202110697625.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-06-23
Publication Date
2026-10-13
Estimated Expiration
2041-06-23

AI Technical Summary

Technical Problem

[0006]本发明为了克服现有电解海水催化剂催化选择性差、稳定性不足的问题,提供一种三维结构铁掺杂钴钼氧化物复合材料及其制备方法,在含氯条件下具有较高的氢析出和氧析出的电催化活性和稳定性,远优于商业Pt/C和IrO2催化剂,制备方法成本低

Benefits of technology

[0015]本发明还提供一种上述制备方法制得的三维结构铁掺杂钴钼氧化物复合材料,结构式为Fe-CoO/Co2Mo3O8/MoO3@NF。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003129161290000011
    Figure HDA0003129161290000011
  • Figure HDA0003129161290000012
    Figure HDA0003129161290000012
  • Figure HDA0003129161290000021
    Figure HDA0003129161290000021
Patent Text Reader

Abstract

The present application relates to the technical field of nanomaterials, and aims to solve the problems of poor catalytic selectivity and insufficient stability of an electrolytic seawater catalyst, and provides a three-dimensional structure iron-doped cobalt-molybdenum oxide composite material and a preparation method thereof, wherein a precursor material Co-MOF@NF is first prepared; then the precursor material is further subjected to a solvothermal method in a mixed solution of molybdate and ferric salt, and a metal ion-doped MOF derivative material is obtained after reaction; then the MOF derivative material is placed in a reducing atmosphere, and a two-stage temperature rise is performed to obtain the iron-doped cobalt-molybdenum oxide composite material. The three-dimensional structure iron-doped cobalt-molybdenum oxide composite material has high hydrogen evolution and oxygen evolution electrocatalytic activity and stability under a chlorine-containing condition, and is far superior to commercial Pt / C and IrO2 catalysts, and the preparation method has low cost. The present application also provides an application of the three-dimensional structure iron-doped cobalt-molybdenum oxide composite material in seawater electrocatalysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nanomaterials technology, and in particular to a three-dimensional iron-doped cobalt-molybdenum oxide composite material, its preparation method, and its application. Background Technology

[0002] Energy issues have always been a major concern for society. Currently, the main energy sources used are non-renewable energy sources such as coal, oil, and natural gas. The non-renewable nature of these energy sources and their serious environmental hazards have forced people to search for a renewable energy source with abundant reserves. Hydrogen, due to its high energy density (142 MJ kg⁻¹) and pollution-free characteristics, has become one of the ideal energy sources to replace traditional fossil fuels. Among the many methods of hydrogen production, water electrolysis has become an important means of achieving industrialized and inexpensive hydrogen production due to its high product purity and high conversion rate (close to 100%). However, large-scale freshwater electrolysis will put heavy pressure on important water resources.

[0003] Seawater is one of the richest natural resources on Earth, accounting for 96.5% of the world's total water resources. Therefore, especially in arid regions, direct electrolysis of seawater instead of freshwater is very important and promising. For example, patent CN112501647A discloses an oxygen evolution reaction catalyst, its preparation, application, electrolysis device, and seawater cracking method. The oxygen evolution reaction catalyst includes a foamed nickel substrate and amorphous / nanocrystalline alkaline iron carbonate supported on the foamed nickel substrate. The amorphous and nanocrystalline mixed structure of alkaline iron carbonate (FeNiCH) contains a large number of surface-adsorbed oxygen and oxygen defects, which may regulate the electronic structure of Fe(III) / Ni(II), optimize the adsorption energy of OER intermediates, and the surface-adsorbed oxygen and defect oxygen may be related to its chloride resistance and high corrosion resistance.

[0004] Due to the presence of chloride ions in seawater, the most significant challenge in seawater pyrolysis occurs at the anode during the chloride evolution reaction (CER), which competes with the oxygen evolution reaction (OER). The CER is a simple two-electron process, resulting in a much faster kinetic rate. A major challenge in this regard is developing stable anodes and improving catalyst selectivity to suppress the CER, thereby promoting seawater electrolysis to achieve optimal performance achievable with freshwater and enabling its widespread application in hydrogen production.

[0005] In recent years, transition metal oxides such as NiO, Co3O4, and MnO2 have been widely studied in water electrolysis due to their advantages such as high rare earth content, low cost, and environmental friendliness. However, their performance is often unsatisfactory because the adsorption energy of the original metal oxides for reaction intermediates is not ideal and their conductivity is poor. Metal doping, by adjusting the electron distribution, is an effective way to promote synergistic effects between ions and improve the intrinsic activity of catalysts. Molybdenum (Mo) is considered to have good corrosion resistance, which has been confirmed in Mo-containing corrosion-resistant alloys and stainless steels. Therefore, developing an electrocatalytic material that can operate under chlorine-containing conditions and has good electrocatalytic performance is of great significance. Summary of the Invention

[0006] To overcome the problems of poor catalytic selectivity and insufficient stability of existing seawater electrolysis catalysts, this invention provides a three-dimensional iron-doped cobalt-molybdenum oxide composite material and its preparation method. Under chlorine-containing conditions, it exhibits high electrocatalytic activity and stability for hydrogen evolution and oxygen evolution, which is far superior to commercial Pt / C and IrO2 catalysts. The preparation method is also low in cost.

[0007] To achieve the above objectives, the present invention adopts the following technical solution: A method for preparing a three-dimensional iron-doped cobalt-molybdenum oxide composite material includes the following steps: 1) Preparation of precursor materials: Prepare methanol solutions of cobalt nitrate hexahydrate and 2-methylimidazole respectively, mix them, add them to conductive nickel foam NF substrate, let stand, and the precursor grows on nickel foam to obtain the precursor material Co-MOF@NF; 2) In a mixed solution of molybdate and iron salt, the precursor material is further reacted using a solvothermal method to obtain metal ion-doped MOF-derived materials. 3) Place the MOF-derived material obtained in step 2) in a reducing atmosphere, heat it to the first stage temperature and hold it for a period of time, then perform a second heating step, heat it to the second stage temperature and hold it for a period of time to obtain an iron-doped cobalt-molybdenum oxide composite material.

[0008] In the synthesis process of this invention, a cobalt metal organic solution is first prepared to grow two-dimensional sheets in situ on an NF substrate. The two-dimensional sheets grown on the conductive substrate are uniformly distributed and of uniform size, providing a good foundation for the subsequent preparation of composite materials. Subsequently, in a solvothermal reaction, smaller two-dimensional nanosheets are etched onto the surface while maintaining the original two-dimensional sheets, increasing the overall specific surface area of ​​the material. In the subsequent reduction and calcination process, some ligands gradually disappear during the first-stage heating process, and the resulting two-dimensional sheets remain relatively stable during the first-stage temperature holding. After the second-stage heating begins, the iron compound portion of the trimetallic component is gradually reduced to form elemental iron, and in situ doping occurs. The iron is uniformly distributed in the two-dimensional sheets, so the reduced elemental iron can directly achieve the purpose of uniform doping. In addition, some high-valence cobalt reacts with the gaseous components in the reducing atmosphere to form new cobalt monoxide, some high-valence molybdenum is not reduced to form molybdenum trioxide, and the remaining cobalt reacts with the molybdenum component to form cobalt molybdate, forming a cobalt monoxide / cobalt molybdate / molybdenum trioxide composite two-dimensional sheet material. This material exhibits excellent catalytic performance in seawater electrolysis and excellent alkali resistance through the synergistic interaction between its components and structure.

[0009] Preferably, the molar ratio of 2-methylimidazole to cobalt nitrate hexahydrate in step 1) is (7-9):1. More preferably, the molar ratio of 2-methylimidazole to cobalt nitrate hexahydrate in step 1) is 8:1. The optimal molar ratio of 2-methylimidazole / metal salt has the best sizing, and changes in the sizing will affect the crystallinity of the synthesized MOF and the stability of the material during subsequent operations.

[0010] Preferably, the growth time in step 1) is 4 hours, and the Co-MOF morphology is a two-dimensional triangular structure.

[0011] Preferably, the molybdate and iron salt in step 2) are NaMoO4·2H2O and Fe(NO3)3·9H2O, respectively, and the solvent is a mixed solution of DMF and deionized water.

[0012] Preferably, the temperature of the solvothermal reaction in step 2) is 100–200°C, and the reaction time is 2–24 h. If the temperature of the solvothermal reaction is too low, the two-dimensional nanosheets cannot be formed because the thermodynamic temperature of the precursor is not reached. The optimal temperature for the solvothermal reaction is 150°C.

[0013] Preferably, the reducing atmosphere in step 2) is a hydrogen and nitrogen atmosphere, wherein the hydrogen content is ≥10% VOL.

[0014] Preferably, in step 3), the heating rate of the first-step heating is 1–10 °C / min; the first-stage temperature is 150–350 °C, and the holding time is 2–4 h; the heating rate of the second-step heating is 1–10 °C / min; the second-stage temperature is 400–700 °C, and the holding time is 2–4 h. However, excessively high second-stage temperatures in a reducing atmosphere can further etch smaller nanosheets in the sample, causing the two-dimensional nanoparticles on the surface to be reduced into clusters, reducing the specific surface area of ​​the material and decreasing the performance of the catalytic reaction.

[0015] The present invention also provides a three-dimensional iron-doped cobalt-molybdenum oxide composite material prepared by the above preparation method, with the structural formula Fe-CoO / Co2Mo3O8 / MoO3@NF.

[0016] This invention also provides the application of the three-dimensional iron-doped cobalt-molybdenum oxide composite material prepared by the above method in seawater electrocatalysis.

[0017] Therefore, the beneficial effects of this invention are as follows: 1) The preparation is simple and efficient, with low equipment requirements, making it easy to promote and realize industrial production; 2) It has dual functions of hydrogen evolution and oxygen evolution, and does not need to be coated on the electrode, so it can be used directly as a self-supporting electrode, which has wide applicability; 3) The obtained three-dimensional iron-doped cobalt-molybdenum oxide composite material has a stable microstructure, uniform nanostructure size, and uniform component distribution, and has good electrocatalytic performance and mechanical properties; 4) It can produce better electrocatalytic effects under alkaline and seawater conditions; 5) The obtained three-dimensional iron-doped cobalt-molybdenum oxide composite material has high electrocatalytic activity and stability for hydrogen evolution and oxygen evolution under chlorine-containing conditions, which is far superior to commercial Pt / C and IrO2 catalysts, and the cost is lower. Attached Figure Description

[0018] Figure 1 The images show the morphological structure of Fe-CoO / Co2Mo3O8 / MoO3@NF prepared in Example 1. Figure 2 The XRD pattern of Fe-CoO / Co2Mo3O8 / MoO3@NF prepared in Example 1; Figure 3 The graph shows the OER and HER performance of Fe-CoO / Co2Mo3O8 / MoO3@NF prepared in Example 1 in alkaline solution. Figure 4 The graph shows the performance test results of Fe-CoO / Co2Mo3O8 / MoO3@NF prepared in Example 1 under alkaline chlorine-containing conditions. Figure 5 The morphological structure of Fe-CoO / Co2Mo3O8 / MoO3-0.4@NF prepared in Example 2 is shown in the following figures. Figure 6 The images show the morphological structure of Fe-CoO / Co2Mo3O8 / MoO3-2@NF-150 prepared in Example 3. Figure 7 The morphological structure of Fe-CoO / Co2Mo3O8 / MoO3@NF-130 prepared in Example 3 is shown in the following figures. Figure 8 The images show the morphological structure of Fe-CoO / Co2Mo3O8 / MoO3@NF-550 prepared in Example 3. Detailed Implementation

[0019] The technical solution of the present invention will be further described below through specific embodiments.

[0020] In this invention, unless otherwise specified, the raw materials and equipment used can be purchased from the market or are commonly used in the field. The methods in the embodiments, unless otherwise specified, are conventional methods in the field.

[0021] Example 1 A method for preparing a three-dimensional iron-doped cobalt-molybdenum oxide composite material includes the following steps: 1) Weigh 0.5g Co(NO3)2·6H2O and 1.3g 2-methylimidazole and dissolve them in 80mL of deionized water to prepare a metal-organic solution. Add nickel foam to the solution and let it stand for 4h. After the nickel foam that has grown the precursor is removed, wash it with deionized water and dry it to obtain the MOF precursor material Co-MOF@NF. 2) Weigh 64 mg NaMoO4·2H2O and 13 mg Fe(NO3)3·9H2O into a mixed solution of 14 mL DMF and 1 mL deionized water. Place the Co-MOF@NF obtained in step 1) into a reaction vessel and carry out a hydrothermal reaction at 150 °C for 6 h. After the solvothermal reaction, metal-doped MOF-derived materials are obtained. 3) After the metal-doped MOF-derived material has naturally cooled to room temperature, it is placed in a hydrogen / nitrogen mixed gas with a hydrogen content of 10% VOL. The temperature is increased in one step at a rate of 10°C / min to a first-stage temperature of 280°C, and held for 2 hours. Then, a second-step heating process is performed at a rate of 10°C / min, increasing the temperature to a second-stage temperature of 450°C, and held for 2 hours. The material is then cooled to room temperature to obtain a three-dimensional iron-doped cobalt-molybdenum oxide composite material. The three-dimensional iron-doped cobalt-molybdenum oxide composite material prepared in this embodiment is labeled as Fe-CoO / Co2Mo3O8 / MoO3@NF. Figure 1 As shown, Figure 1(a) is a SEM image of Fe-CoO / Co2Mo3O8 / MoO3@NF. As can be seen from the image, the two-dimensional sheet of Fe-CoO / Co2Mo3O8 / MoO3@NF is vertically grown on a nickel foam substrate. The thickness of the two-dimensional sheet is about 500 nm, while the nanosheets on the surface are about 15 nm thick. Figure 1 (b) TEM image of Fe-CoO / Co2Mo3O8 / MoO3@NF is shown, which shows the nanosheet structure on the surface of Fe-CoO / Co2Mo3O8 / MoO3@NF; Figure 1 (c) is the transmission elemental distribution diagram of Fe-CoO / Co2Mo3O8 / MoO3@NF. It can be seen that in addition to Co and Mo, Fe is also uniformly distributed in the nanosheets, and the composition is uniform. Figure 2 The obtained Fe-CoO / Co2Mo3O8 / MoO3@NF material exhibits good crystallinity. Comparison with the PDF cards shows that they correspond to CoO, Co2Mo3O8, and MoO3, respectively, indicating successful synthesis of the Fe-CoO / Co2Mo3O8 / MoO3@NF material. Subsequent OER and HER performance tests were conducted. Figure 3 (a) It can be seen that the OER performance test was conducted in 1M KOH at a current density of 20 mA / cm². 2 At that time, the potential of Fe-CoO / Co2Mo3O8 / MoO3@NF was only 1.53V, which is far superior to the potential of commercial IrO2, demonstrating excellent OER performance; Figure 3 (b) It can be seen that HER performance testing was performed in 1M KOH at a current density of -10 mA / cm². 2 At this time, the potential of Fe-CoO / Co2Mo3O8 / MoO3@NF is only -0.087V, which is very close to that of commercially available Pt / C catalysts. Figure 4 (a) shows the polarization curves of the Fe-CoO / Co2Mo3O8 / MoO3@NF||Fe-CoO / Co2Mo3O8 / MoO3@NF assembled catalyst in alkaline simulated seawater and alkaline seawater solutions. It can be seen that at a current density of 10 mA·cm⁻¹, the polarization curves are... -2 The measured cell voltages were 1.576V and 1.593V, indicating that the material can still maintain good performance under chlorine-containing conditions. Figure 4 (b) To detect the hydrogen and oxygen production of the catalyst under chlorine-containing conditions, it can be seen that the actual measured gas volume basically coincides with the theoretical value, indicating that our material has excellent selectivity. Through the above characterization and testing, it is clear that the Fe-CoO / Co2Mo3O8 / MoO3@NF three-dimensional iron-doped cobalt-molybdenum oxide composite material prepared in this embodiment has good electrocatalytic performance, good structural stability, and good compositional homogeneity. It can be used for seawater electrocatalysis.

[0022] Example 2 A method for preparing a three-dimensional iron-doped cobalt-molybdenum oxide composite material, the method comprising the following preparation steps: 1) Weigh 0.5g Co(NO3)2·6H2O and 1.3g 2-methylimidazole and dissolve them in 80mL of deionized water to prepare a metal-organic solution. Add nickel foam to the solution and let it stand for 4h. After the nickel foam that has grown the precursor is removed, wash it with deionized water and dry it to obtain the MOF precursor. 2) Weigh 40 mg NaMoO4·2H2O and 7.2 mg Fe(NO3)3·9H2O into a mixed solution of 14 mL DMF and 5 mL deionized water. Then place the above MOF precursor in a reactor for hydrothermal reaction at 150 °C for 6 h. After solvothermal reaction, metal-doped MOF-derived materials are obtained. 3) After the metal-doped MOF-derived material naturally cools to room temperature, it is placed in a hydrogen / nitrogen mixed gas with a hydrogen content of 10% VOL. The temperature is increased in one step at a rate of 10°C / min to a first-stage temperature of 280°C and held for 2 hours. Then, a second-step heating process is performed at a rate of 10°C / min to a second-stage temperature of 500°C and held for 2 hours. After cooling to room temperature, a three-dimensional iron-doped cobalt-molybdenum oxide composite material is obtained. This three-dimensional iron-doped cobalt-molybdenum oxide composite material is labeled as Fe-CoO / Co2Mo3O8 / MoO3-0.4@NF. The SEM image of Fe-CoO / Co2Mo3O8 / MoO3-0.4@NF obtained in Example 2 is shown below. Figure 5 As shown, the Fe-CoO / Co2Mo3O8 / MoO3-0.4@NF two-dimensional sheet is vertically grown on a nickel foam substrate. The thickness of the two-dimensional sheet is about 500 nm, and the surface has a large number of crisscrossing nanosheets.

[0023] Example 3 A method for preparing a three-dimensional iron-doped cobalt-molybdenum oxide composite material, the method comprising the following preparation steps: 1) Weigh 0.5g Co(NO3)2·6H2O and 1.3g 2-methylimidazole and dissolve them in 80mL of deionized water to prepare a metal-organic solution. Add nickel foam to the solution and let it stand for 4h. After the nickel foam that has grown the precursor is removed, wash it with deionized water and dry it to obtain the MOF precursor. 2) Weigh 120 mg NaMoO4·2H2O and 21 mg Fe(NO3)3·9H2O into a mixed solution of 14 mL DMF and 5 mL deionized water. Then place the above MOF precursor in a reactor for hydrothermal reaction at 150 °C for 6 h. After solvothermal reaction, metal-doped MOF-derived materials are obtained. 3) After the metal-doped MOF-derived material naturally cools to room temperature, it is placed in a hydrogen / nitrogen mixed gas with a hydrogen content of 10% VOL. The temperature is increased in one step at a rate of 10℃ / min to a first-stage temperature of 280℃, and held for 2 hours. Then, a second-step heating process is performed at a rate of 10℃ / min to a second-stage temperature of 500℃, which is held for 2 hours. After cooling to room temperature, a three-dimensional iron-doped cobalt-molybdenum oxide composite material is obtained. This three-dimensional iron-doped cobalt-molybdenum oxide composite material is labeled as Fe-CoO / Co2Mo3O8 / MoO3-2@NF. The SEM image of Fe-CoO / Co2Mo3O8 / MoO3-2@NF obtained in Example 3 is shown below. Figure 6 As shown, the Fe-CoO / Co2Mo3O8 / MoO3-2@NF two-dimensional sheet is vertically grown on a nickel foam substrate. The thickness of the two-dimensional sheet is about 500 nm, and the surface has a large number of crisscrossing nanosheets.

[0024] Comparative Example 1 A method for preparing a three-dimensional iron-doped cobalt-molybdenum oxide composite material, compared with Example 1, differs only in that the hydrothermal reaction temperature in step 2) is changed from 150℃ to 130℃, while all other steps remain unchanged. Figure 7 It can be seen that no two-dimensional nanosheets appeared on its surface.

[0025] Comparative Example 2 A method for preparing a three-dimensional iron-doped cobalt-molybdenum oxide composite material, compared with Example 1, differs only in that the second-order temperature in step 3) is changed from 450℃ to 550℃, while the others remain unchanged. Figure 8 It can be seen that the two-dimensional nanosheets on its surface are destroyed due to excessive temperature.

[0026] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A method for preparing a three-dimensional iron-doped cobalt-molybdenum oxide composite material, characterized in that, Includes the following steps: 1) Preparation of precursor materials: Prepare methanol solutions of cobalt nitrate hexahydrate and 2-methylimidazole respectively, mix them, add them to conductive nickel foam NF substrate, let stand, and the precursor grows on nickel foam to obtain the precursor material Co-MOF@NF; 2) In a mixed solution of molybdate and iron salt, the precursor material is further reacted using a solvothermal method to obtain a metal ion-doped MOF-derived material; the solvent for the solvothermal reaction is a mixed solution of DMF and deionized water. 3) Place the MOF-derived material obtained in step 2) in a reducing atmosphere, heat it to the first stage temperature and hold it for a period of time, then perform a second heating step, heat it to the second stage temperature and hold it for a period of time to obtain an iron-doped cobalt-molybdenum oxide composite material. The structural formula of the iron-doped cobalt-molybdenum oxide composite material is Fe-CoO / Co2Mo3O8 / MoO3@NF. The iron-doped cobalt-molybdenum oxide composite material obtained in step 3) was applied to seawater electrocatalysis.

2. The method for preparing a three-dimensional iron-doped cobalt-molybdenum oxide composite material according to claim 1, characterized in that, In step 1), the molar ratio of 2-methylimidazole to cobalt nitrate hexahydrate is (7-9):

1.

3. The method for preparing a three-dimensional iron-doped cobalt-molybdenum oxide composite material according to claim 1, characterized in that, In step 2), the molybdate and iron salt are selected as NaMoO4·2H2O and Fe(NO3)3·9H2O, respectively.

4. The method for preparing a three-dimensional iron-doped cobalt-molybdenum oxide composite material according to claim 1, characterized in that, The temperature of the solvothermal reaction is 100–200°C, and the reaction time is 2–24 h.

5. A method for preparing a three-dimensional iron-doped cobalt-molybdenum oxide composite material according to claim 1 or 3, characterized in that, Step 3) The reducing atmosphere is a hydrogen and nitrogen atmosphere, wherein the hydrogen content is ≥10% VOL.

6. The method for preparing a three-dimensional iron-doped cobalt-molybdenum oxide composite material according to claim 1, characterized in that, Step 3) The heating rate of the first stage is 1-10℃ / min; the temperature of the first stage is 150-350℃, and the holding time is 2-4h; the heating rate of the second stage is 1-10℃ / min; the temperature of the second stage is 400-700℃, and the holding time is 2-4h.

Citation Information

Patent Citations

  • Preparation method of molybdenum-doped cobalt-iron oxide nano-sheet bifunctional electrocatalyst

    CN110227531A

  • NiCoP / NiCo-DHatNF composite material, and preparation method and application thereof

    CN112156798A